Energetic Requirements for Egg-Laying Bobwhites - Ronald M. Case (National Quail Symposium Proceedings, 2017)
As part of an extensive bioenergetics study of bobwhite quail (Colinus virginianus), energy requirements for egg laying were determined. Caloric values for eggs averaged 5.489 kcal/g. Net energetic efficiency of converting productive energy into eggs was conservatively estimated to be 54% for quail laying at a rate of 0.45 egg/bird-day at 25 C. Assuming that those values were the same for quail laying a 10-g egg at a rate of 1 egg/bird-day resulted in an energy requirement of 69.645 kcal/bird-day. This is an energy demand equivalent to that of existence alone at about -3.3 C